Bioaerosol deposition on an air-conditioning cooling coil. (November 2016) - Wu, Yan; Chen, Ailu; Luhung, Irvan; Gall, Elliott T.; Cao, Qingliang; Chang, Victor Wei-Chung; Nazaroff, William W
Abstract: This study is concerned with the role of a fin-and-tube heat exchanger in modifying microbial indoor air quality. Specifically, depositional losses of ambient bioaerosols and particles onto dry (not cooled) and wet (cool) coil surfaces were measured for different airspeeds passing through the test coil. Total, bacterial and fungal DNA concentrations in condensate water produced by a wet coil were also quantified by means of fluorescent dsDNA-binding dye and qPCR assays. Results revealed that the deposition of bioaerosols and total particles is substantial on coil surfaces, especially when wet and cool. The average deposition fraction was 0.14 for total DNA, 0.18 for bacterial DNA and 0.22 for fungal DNA on the dry coil, increasing to 0.51 for total DNA, 0.50 for bacterial DNA and 0.68 for fungal DNA on the wet coil. Overall, as expected, deposition fractions increased with increasing particle size and increasing airspeed. Deposited DNA was removed from the cooling coil surfaces through the flow of condensing water at a rate comparable to the rate of direct deposition from air. A downward trend of bacterial and fungal DNA measured in condensate water over time provides suggestive evidence of biological growth on heat exchangers during nonoperational times of a ventilation system. This investigation provides new information about bioaerosol deposition onto a conventional fin-and-tube cooling coil, a potentially important factor influencing indoor exposure to microbial aerosols in air-conditioned buildings. Highlights: Deposition behavior to cooling coil is similar for bacterial and fungal bioaerosol. Bioaerosol deposition is enhanced by the presence of water condensation. Deposition of DNA to coil is approximately balanced by removal from water drainage. Viable microbes appear to reproduce on coil surface during periods of inoperation.